2019
DOI: 10.1371/journal.pgen.1008397
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin dynamics enable transcriptional rhythms in the cnidarian Nematostella vectensis

Abstract: In animals, circadian rhythms are driven by oscillations in transcription, translation, and proteasomal degradation of highly conserved genes, resulting in diel cycles in the expression of numerous clock-regulated genes. Transcription is largely regulated through the binding of transcription factors to cis-regulatory elements within accessible regions of the chromatin. Chromatin remodeling is linked to circadian regulation in mammals, but it is unknown whether cycles in chromatin accessibility are a general fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Owing to this, their divergence at the base of metazoans, where major evolutionary transitions took place with respect to developmental processes such as axis pattering and cell type functions, is poorly understood. Until now very few studies have reported the identification of the enhancer elements from the basal metazoan phylum Cnidaria suggesting their roles in gene regulation in different paradigms [ 31 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this, their divergence at the base of metazoans, where major evolutionary transitions took place with respect to developmental processes such as axis pattering and cell type functions, is poorly understood. Until now very few studies have reported the identification of the enhancer elements from the basal metazoan phylum Cnidaria suggesting their roles in gene regulation in different paradigms [ 31 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is little knowledge about the relationship between promoter accessibility and its related gene expression, as various regulatory mechanisms can regulate cnidarian gene activity. For example, we have previously shown that clock-controlled genes present different accessibility patterns over a 24 h period [ 22 ]. It was found that promoters of some clock-controlled genes were constantly accessible, whereas the accessibility of others oscillated [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have previously shown that clock-controlled genes present different accessibility patterns over a 24 h period [ 22 ]. It was found that promoters of some clock-controlled genes were constantly accessible, whereas the accessibility of others oscillated [ 22 ]. Further research is needed in the field of epigenetics and, more specifically, on chromatin spatial interactions, in order to elucidate how promoter accessibility is linked with changes in gene expression in cnidarians.…”
Section: Discussionmentioning
confidence: 99%
“…ATAC-seq mapping in neurons of the cnidarian N. vectensis revealed neuron-specific gene accessibility patterns that correlated with neuronal transcription profiles ( Sebé-Pedrós et al, 2018 ). A positive correlation between gene accessibility and transcription has been observed for most circadian rhythm-regulated gene promoters in the starlet sea anemone N. vectensis , which also has distal regions with enhancer-like properties, and thermal stress-responsive genes in the coral Aiptasia pallida ( Weizman and Levy, 2019 ; Weizman et al, 2019 ). In a recent study, Reddy et al (2020b) showed that unlike in higher metazoans, RNA Pol II does not pause at the TSSs of most genes in H. vulgaris Ind-Pune and is instead uniformly distributed across gene bodies, with its occupancy positively correlated with the expression level.…”
Section: Chromatin Organizationmentioning
confidence: 99%
“…This study indicated that bilaterian enhancer characters are conserved in N. vectensis ( Schwaiger et al, 2014 ). Among these, ∼600 enhancers have been shown to play a role in transcription regulation associated with the circadian rhythms ( Weizman et al, 2019 ). In Hydra , Wnt signaling has been shown to play a vital role in the organizer formation and is associated with massive transcriptional changes ( Reddy et al, 2019 ).…”
Section: Cis -Regulatory Elementsmentioning
confidence: 99%